Transfer phenomena in fluid and heat flows XII : Special topic volume with invited peer reviewed papers only - Kolisnychenko, Stanislav (Diffusion and defect data. Defect and diffusion forum ;, 2021)
Special topic volume with invited peer reviewed papers only.